2021
DOI: 10.1111/2047-3095.12350
|View full text |Cite
|
Sign up to set email alerts
|

Reflective practice in nursing: A concept analysis

Abstract: This paper aims to clarify the concept of reflective practice in nursing by using Rodgers' evolutionary method of concept analysis.Data sources: Literature and references on the concept of reflective practice were obtained from two databases: Scopus and Nursing and Allied health database. Peerreviewed articles published in English language between 2011-2021 that included the terms 'reflection' and/or 'reflective practice' in the title were selected. Seminal pieces of work were also considered in this analysis.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 29 publications
(181 reference statements)
0
16
0
Order By: Relevance
“…As far as we know, there is no literature that investigated the effects of reflective practices in this field, such as intervision or peer review, on these specific outcomes. It is known that reflective practice translates experience into knowledge (Schön, 1983), which is assumed to improve the quality of patient care (Patel & Metersky, 2022). Looking at all benefits mentioned, a regular reflection with peers on the patient needs assessment may indeed have the potential to create more uniform care according to patients’ demand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we know, there is no literature that investigated the effects of reflective practices in this field, such as intervision or peer review, on these specific outcomes. It is known that reflective practice translates experience into knowledge (Schön, 1983), which is assumed to improve the quality of patient care (Patel & Metersky, 2022). Looking at all benefits mentioned, a regular reflection with peers on the patient needs assessment may indeed have the potential to create more uniform care according to patients’ demand.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, there is no literature that investigated the effects of reflective practices in this field, such as intervision or peer review, on these specific outcomes. It is known that reflective practice translates experience into knowledge (Schön, 1983), which is assumed to improve the quality of patient care (Patel & Metersky, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The study also found that it can use scientific knowledge, personal knowledge, and experiential knowledge to solve complicated problems in practice [ 3 ]. Moreover, studies have shown that reflective practice, as a cognitive skill that nurses learn from experience, can improve the knowledge and skills of nursing students, novice nurses, and experienced nurses in clinical practice, improve the professional practice of nurses and positively improve the health outcomes of patients [ 1 , 4 ]. It has also been reported that reflective practice can enhance a clinician’s competence through a critical review of clinical practice [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In direct contact with patients in clinical practice, MNS may encounter unexpected clinical situations leading to stress [ 9 ], and most of these clinical experiences have not been effectively addressed. Therefore, reflective practice is necessary for MNS for patient safety [ 4 ] nurses' own physical and mental health, and coping with future challenges [ 4 ]. Reflective practice improves nurses' understanding of their practice by giving meaning to their experiences [ 4 , 10 ], thereby enhancing their personal and nursing professional development [ 2 ], and narrowing the gap between theory and clinical practice in nursing humanistic care dimension [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation